2022
DOI: 10.1101/2022.04.28.489889
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Touch receptor end-organ innervation and function requires sensory neuron expression of the transcription factor Meis2

Abstract: Touch sensation is primarily encoded by mechanoreceptors, sometimes called Low-Threshold Mechanoreceptors (LTMRs), with their cell bodies in the Dorsal Root Ganglia (DRG). LTMRs make up no more that 20% of all sensory neurons and exhibit great diversity in terms of molecular signature, terminal ending morphology and electrophysiological properties, mirroring the complexity of tactile experience. LTMRs are an interesting model to study the molecular cues controlling neuronal diversification in terms of both mol… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 102 publications
(388 reference statements)
5
12
0
Order By: Relevance
“…In our mouse model, we could not evidence any neuronal loss of vagal neurons of the JNG, suggesting that Meis2 inactivation does not affect neuronal survival or identity as demonstrated by the normal expression of Ntrk2, Ntrk3 and Ret. These results are in line with our previous studies on Meis1 or Meis2 inactivation in different types of peripheral neurons 31,36 . When Meis1 is specifically inactivated in sympathetic neurons, distal innervation of target organs, including the heart, is compromised, but early sympathetic specification is unaffected 31 .…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…In our mouse model, we could not evidence any neuronal loss of vagal neurons of the JNG, suggesting that Meis2 inactivation does not affect neuronal survival or identity as demonstrated by the normal expression of Ntrk2, Ntrk3 and Ret. These results are in line with our previous studies on Meis1 or Meis2 inactivation in different types of peripheral neurons 31,36 . When Meis1 is specifically inactivated in sympathetic neurons, distal innervation of target organs, including the heart, is compromised, but early sympathetic specification is unaffected 31 .…”
Section: Discussionsupporting
confidence: 94%
“…More recently, we found that Meis2 inactivation in postmitotic peripheral sensory neurons dictates comparable phenotypes for DRG touch neurons with incomplete distal innervation, impaired electrophysiological responses to mechanical stimuli and reduced touch sensation 36 . In the present study, because Meis2 is essential for normal heart development, we took advantage of the same mouse strain as used previously to investigate, independently of cardiac malformations, if Meis2 targeted inactivation in peripheral sensory neurons also recapitulates some of the cardiac sympatho-vagal imbalance phenotypes reported in ASD studies.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations